"Here to Support Anybody Who Needs to Come?" An Investigation of the Provision for EAL Pupils in Secondary School Libraries in England. Issue 1 (2nd January 2017) - Badock, Anja; Birdi, Briony
ABSTRACT: This article presents the findings of a mixed methods investigation of the effectiveness of provision for EAL pupils by secondary school libraries in England. Data from a quantitative survey of secondary school librarians are triangulated with those of qualitative interviews with staff responsible for EAL provision. A picture emerges of a hybrid environment that addresses a number of the educational, cultural, and social needs of EAL learners, but in which a series of barriers to effective provision are also identified. Recommendations are made to key stakeholder groups for the short and long term improvement of EAL provision, and for further research.